Identifying barriers for nature-based solutions in flood risk management: An interdisciplinary overview using expert community approach. (15th May 2022) - Raška, Pavel; Bezak, Nejc; Ferreira, Carla S.S.; Kalantari, Zahra; Banasik, Kazimierz; Bertola, Miriam; Bourke, Mary; Cerdà, Artemi; Davids, Peter; Madruga de Brito, Mariana; Evans, Rhys; Finger, David C.; et al.
Abstract: The major event that hit Europe in summer 2021 reminds society that floods are recurrent and among the costliest and deadliest natural hazards. The long-term flood risk management (FRM) efforts preferring sole technical measures to prevent and mitigate floods have shown to be not sufficiently effective and sensitive to the environment. Nature-Based Solutions (NBS) mark a recent paradigm shift of FRM towards solutions that use nature-derived features, processes and management options to improve water retention and mitigate floods. Yet, the empirical evidence on the effects of NBS across various settings remains fragmented and their implementation faces a series of institutional barriers. In this paper, we adopt a community expert perspective drawing upon LAND4FLOOD Natural flood retention on private land network (https://www.land4flood.eu ) in order to identify a set of barriers and their cascading and compound interactions relevant to individual NBS. The experts identified a comprehensive set of 17 barriers affecting the implementation of 12 groups of NBS in both urban and rural settings in five European regional environmental domains (i.e., Boreal, Atlantic, Continental, Alpine-Carpathian, and Mediterranean). Based on the results, we define avenues for further research, connecting hydrology and soil science, on the one hand, and land use planning, social geography and economics, on the other. Our suggestions ultimately call for a transdisciplinary turn in the research of NBS in FRM. Graphical abstract: Image 1 Highlights: The European expert community perspective on nature-based solutions is presented. 12 groups of nature-based solutions relevant to flood risk management are defined. 17 implementation barriers for the 12 nature-based-solution groups are identified. Cascading and compound barriers call for a transdisciplinary approach to floods.